Evaluation of visual outcomes with toric intraocular lens implantation using digital marker during cataract surgery - Jeeva, Irfan Kabiruddin; Masud, Sidra; Saeed Ali, Tazeen; Siddiqui, Muhammad Abdul Rehman; Waheed, Ayesha Akbar; Awan, Amna (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the visual improvement and mean residual astigmatism in patients who underwent cataract surgery with toric intraocular lens. Method: The retrospective, observational study was conducted at the Department of Ophthalmology, Aga Khan University Hospital, Karachi, and comprised data from January 1, 2018, to December 31, 2020, related to adult patients who had regular astigmatism of at least 0.75D and underwent cataract surgery with toric intraocular lens implantation using a digital marker. The patients were followed up on post-operative days 1, 7, 30, 90 and 180. Along with age, the degree of astigmatism was noted. The visual acuity was calculated pre- and post-operatively. The mean residual astigmatism was then noted for all patients post-operatively. Data was analysed using SPSS 22. Results: The sample comprised 240 eyes of 177 patients; 99(55.9%) males and 78(44.1%) females. The mean age of the sample was 62.5±10.6 years. The mean unaided visual acuity improved post-operatively from 0.57±0.38 to 0.07±0.22 at 90 days. At the 30-day follow-up, mean residual astigmatism had reduced from 1.52±0.84 to 0.01±0.09 (p<0.001). The mean intraocular lens rotation from the intended axis was 0.73°±0.92° on day 30. Conclusion: Toric intraocular lens implantation using a digital marker could effectively reduce the post-operative cylinder, and improve the unaided visual acuity following cataract surgery. Key Words: Intraocular lens implantation, Cataract, Toric IOL, Accuracy of toric IOL.